Single-molecule dynamics of nuclear mRNA - Shav-Tal, Yaron (Biology Reports Ltd, 2009)
In eukaryotes, mRNA molecules are transcribed from nuclear DNA and commute through a labyrinth of nucleoplasmic passageways to the nuclear envelope where they are exported to the cytoplasm. New findings provide tools and insights into the biophysical properties that govern mRNA translocations en route to the cytoplasm and suggest that mRNA molecules move in a discontinuous manner due to transient interactions with the nuclear environment.